Quantifying the economic cost of invertebrate pests to New Zealand's pastoral industry. Issue 3 (3rd July 2019) - Ferguson, Colin M.; Barratt, Barbara I. P.; Bell, Nigel; Goldson, Stephen L.; Hardwick, Scott; Jackson, Mark; Jackson, Trevor A.; Phillips, Craig B.; Popay, Alison J.; Rennie, Grant; Sinclair, Stephen; Townsend, Richard; et al.
ABSTRACT: The invertebrate pests most commonly affecting New Zealand's pastoral-based production in 'average' years cause losses of between $1.7B and $2.3B p.a. of which up to $0.9B occur on sheep and beef farms and $1.4B on dairy farms. The native scarab grass grub is the most costly pest causing losses of $140–380 M on dairy farms and $75–205 M on sheep and beef farms annually. The exotic scarab, black beetle, although only affecting approximately 1 M ha, costs dairy farmers up to $223 M and sheep and beef farmers up to $19 M annually. Porina cause losses up to $84 M and $88 M respectively. Pasture nematodes are estimated to cost up to $274 M p.a. for dairy farmers and $326 M p.a. for sheep and beef farmers. Two exotic pests, Argentine stem weevil (ASW) and clover root weevil (CRW) are causing damage estimated at up to $200 M p.a. and $235 M p.a. respectively in dairy and sheep and beef pastures. While CRW is subject to successful biological control management it still causes considerable losses. Lesser pests also contribute to lost production, particularly as they often coexist with more major pests. However, their economic cost to New Zealand is difficult to calculate due to the variable nature of infestations on both temporal and spatial scales. At farm and paddock level, it is abundantly clear that substantial savings could be made if pest management is achieved. It is equally clear that in many instances the tools to do so are limited but if developed would contribute substantially to farm profitability.